HPLC Quantification of Cytotoxic Compounds from Aspergillus niger - Paula Karina S. Uchoa; Leandro Bezerra de Lima; Antonia T. A. Pimenta; Maria da Conceição F. de Oliveira; Jair Mafezoli; Mary Anne S. Lima (Journal of Chemistry)
A high-performance liquid chromatography method was developed and validated for the quantification of the cytotoxic compounds produced by a marine strain of Aspergillus niger. The fungus was grown in malt peptone dextrose (MPD), potato dextrose yeast (PDY), and mannitol peptone yeast (MnPY) media during 7, 14, 21, and 28 days, and the natural products were identified by standard compounds. The validation parameters obtained were selectivity, linearity (coefficient of correlation > 0.99), precision (relative standard deviation below 5%), and accuracy (recovery > 96).